2009
DOI: 10.1007/s11062-009-9093-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in EEG Rhythms and Spike Activity of Brainstem Dopaminergic Neurons Induced by Neurofeedback Sessions in Cats

Abstract: We examined the dynamics of the ratios of spectral power densities (SPDs) of the alpha vs theta rhythms (α/θ ratio)  of EEG and of the spiking frequency of supposedly dopaminergic (DA) neurons of the ventral tegmentum in the course of neurofeedback sessions directed toward changes in the EEG characteristics. Trainings were performed using techniques analogous to that used in neurofeedback sessions in humans. The level of the noise acoustic signal presented to the animal decreased with increase in the α/θ rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
3
1
Order By: Relevance
“…Therefore, our experiments demonstrated that EEG-FB sessions are accompanied by moderate but rather clearly expressed intensification of the spike activity of LC NA neurons. These modifications differed from transformations of the activity of DA cells observed in the same experimental situation [5]. Statistically significant changes in the frequency of spiking of LC NA neurons was manifested at the 1st min of the action of the feedback signal, i.e., noticeably earlier (by about 1 min).…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…Therefore, our experiments demonstrated that EEG-FB sessions are accompanied by moderate but rather clearly expressed intensification of the spike activity of LC NA neurons. These modifications differed from transformations of the activity of DA cells observed in the same experimental situation [5]. Statistically significant changes in the frequency of spiking of LC NA neurons was manifested at the 1st min of the action of the feedback signal, i.e., noticeably earlier (by about 1 min).…”
Section: Resultscontrasting
confidence: 59%
“…Thus, not only activation of DA neurons in the ventral tegmentum [5], but also creation of a relatively increased NA level in sufficiently extensive cerebral regions, is one of the crucial factors determining the efficacy of EEG-FB sessions. These events lead to simultaneous modification of the state of great neuronal populations related to the formation of the EEG α rhythm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations